More than you wanted to know about John Baldessari - Baldessari, John (Zurich : JRP Ringier Kunstverl., 2013)
This title is the first complete collection of the writings of artist John Baldessari. The texts in this two-volume set trace the development of Baldessari's understanding of art from the early 1960s through the present, and includes an extended interview with the artist on the subject of his writing.
boek